The definitive guide to SQLite - Allen, Grant (Expert's voice in open source., 2010)
Outside of the world of enterprise computing there is one database that enables a huge range of software and hardware to flex relational database capabilities, without the baggage and cost of traditional database management systems. That database is SQLite - an embeddable database with an amazingly small footprint, yet it can handle databases of enormous size. SQLite comes equipped with an array of powerful features available through a host of programming and development environments. It is supported by languages such as C, Java, Perl, PHP, Python, Ruby, TCL, and more. The Definitive Guide to.